Portal m-Da’wah using Wireless Application Protocol - Prasetyawan, Daru; Yazid, Ahmad Subhan; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2013)
Information and technology develop quickly, cannot be controlled. This development has an impact on almost all sectors of human life, ranging from the academic sector, government, economy, military, to the household order. Technological developments also reach human affairs in religion. In every religion, there is guidance to remind one another and invite others to the good. This is often known as da'wah. Da'wah for Muslims is one of the obligations that must be carried out. This study aims to build a mobile application as a propaganda media by implementing wireless protocols. The study method used in this study is system development, which is an experiment for the design of the m-da?wah portal that can be accessed via a cellphone or PDA. Da'wah mobile applications are built with the PHP programming language, HTML tags, and WML tags, as well as utilizing the MySQL database as a database server, and implemented through the GPRS network (General Pocket Radio System), so we need a mobile phone or PDA equipped with WAP facilities to access the application. The m-da?wah application has the ability to make it easy for users to obtain Islamic articles that can be easily understood by readers and is equipped with a zakat counter facility that can be accessed via a cellphone or PDA. The test results show that the application meets the functionality requirements and is suitable for use.